FIRST LANGUAGE TEACHERS’ DEVELOPMENT: LEARNING FROM SMALL-SCALE CLASSROOM RESEARCH - Coimbra, Maria De Nazaré Castro Trigo; Alves, Carla Dimitre Dias (PUPIL: International Journal of Teaching, Education and Learning, 2017)
This study aims at analysing how small-scale classroom research can improve professional development of first language teachers, as well as promotes students’ reading and writing skills. The research took place in four elementary and secondary schools of northern of Portugal, in the academic year 2015/16, during two continuous training courses for first language teachers. The qualitative approach focused on the analysis of fifty teachers´ reports of their classroom research project, including the pedagogical intervention process, the results achieved and exemplification of students´ work and written comments. The results show teachers’ awareness of small-scale classroom research, viewed as essential to deepen the understanding of specific educational realities and contexts and to uphold the quality of teaching. For these reasons, classroom research is considered a strategic tool for the improvement of training and teaching, the stimulation of meaningful learning and academic achievement, and the development of the students´ reading and writing skills. All teachers have confirmed classroom research as a foundation for practical reflectivity, in order to achieve good-quality first language teaching and learning and help students overcome their language difficulties. However, teachers also recognize that classroom research is not yet common practice, since it demands investigation skills and a theoretical and practical framework which many teachers do not, in fact, possess. Therefore, more small-scale research in the classroom is needed, along with collaborative work between peers and pedagogical-didactic updates. Such improvements would promote teachers´ professional development as well as students´ reading and writing skills, within the dynamics of each school as a learning community.